IDENTIFIKASI JENIS-JENIS BURUNG PANTAI YANG BERMIGRASI DI TANJUNG BUNGA KECAMATAN TELUK PAKEDAI KABUPATEN KUBU RAYA - Tambunan, Martin F; Nurdjali, Bachrun; Siahaan, Sarma (Universitas Tanjungpura, 2016)
Shorebirds area group ofaquatic birds that are ecologically dependent on coastal areas, either as a haven, foraging and breeding (Howes, Bakwell and Noor. 2003). There are some shorebirds that breed away from the beach but still use the beach as a middleman to reach these places. Shorebirds like wetland habitats such as mangrove forests, seagrass beds, mud Hirst (mudflat), estuaries, ponds and rice fields. In general, there are two kinds of key threats to shorebirds in Indonesia, namely use change and habitat destruction and poaching in scale unsustainable. The use of toxins and pesticidesin agriculture is also considered a potential threat to shorebirds. The purpose of research is to determine the types of shorebirds that migrate in Tanjung Bunga Sub-District Teluk Pakedai, District Kubu Raya. Identification Data Type The Migratory Shorebirds can provide information and data to researchers and government agencies in the field of conservation of migratory shorebirds in Tanjung Bunga Sub-District Teluk Pakedai, District Kubu Raya, so it can be made in an effort programming management, protection and preservation in the region. Field observations carried out at 4 observation point is on the muddy shore, the results obtained as many as 22 species of birds are classified into 9 families and included in the 5 order, of 22 type were found 12 species is a group of shorebirds and 10 specie sof birds belonging to the local, as well as 11 species of birds among the 22 newly discovered species protected by the Law of the Republic of IndonesiaKeyword : Identification, migration, shorebird.If Full Text Pdf error, please use the link to acces : https://drive.google.com/file/d/0B2fYVAKSai7wYVRteGtSMXhXcDA/view